A 5-year review of recurrent pelvic organ prolapse following pelvic reconstructive surgeries in Hospital Sultanah Nur Zahirah - Sulaiman, Sukainah (2020)
Recurrent pelvic organ prolapse after primary pelvic reconstructive surgery is common with recurrence rate 29-34%. The study was carried out to determine the local prevalence of recurrent pelvic organ prolapse (POP) and to determine the associated factors for its recurrence following primary pelvic reconstructive surgery (PRS). It was a retrospective observational study which was carried out at Hospital Sultanah Nur Zahirah, Kuala Terengganu involving all patient who underwent PRS between 1st January 2011 and 31st December 2015. Case notes were review and patients who had recurrent POP more or equal to grade 2 Baden-Walker System within two years of the operation were included. A total of 125 patients were involved. The prevalence of recurrent POP following primary PRS in studied population was 24.8%. The association between each related variable towards recurrent POP was examined. However, no variables were found to be significant at the end. The prevalence of recurrent pelvic organ prolapse in HSNZ was 24.8% within two years interval between primary operation and recurrence. There were no significant risk factors identified to be associated with the recurrence in the studied population. However, the age was the nearest factor that influence recurrence of POP.